Higher Education and Brussels - Joost Vaesen; Benjamin Wayens (Brussels Studies)
This synopsis is the first attempt until now to make a global assessment of the role and importance of higher education in Brussels in its interactions with the city and urban development.This synopsis includes three distinct parts. The first part defines the Belgian institutional and political framework of higher education institutions in Brussels. The second establishes a series of observations. The third part discusses some major challenges and debates regarding higher education institutions in Brussels.